PENGATURAN OBJEK BARANG KENA CUKAI DALAM PERSPEKTIF NEGARA KESEJAHTERAAN - Bulkiah, Bulkiah; Syahbandir, Mahdi; Yani, Teuku Ahmad (LITIGASI, 2022)
Legal policy governing goods subject to excise in the perspective of welfare state is a regulation enacted by the state in order to control the circulation and the use of certain goods affected the community health and the environment which in the end is leading to welfare. The regulation has caused problems since there were different and conflicting cross-sectoral interests. The findings of the research showed that the regulation on the goods subject to excise in the perspective of welfare state is applied through extensification of the excisable goods and the application and renewal of the excise tariff. General regulation applies by arranging provisions on controlling and handling impact of the goods subject to excise. The regulation gives power to the regional government to manage the profit sharing for the health service and welfare improvement for the community. Keywords : Legal policy, Excisable goods, Welfare State.